Exploring the effects of volcanic eruption disturbances on the soil microbial communities in the montane meadow steppe. (December 2020) - Chen, Jin; Guo, Yuqing; Li, Fansheng; Zheng, Yaxin; Xu, Daolong; Liu, Haijing; Liu, Xinyan; Wang, Xinyu; Bao, Yuying
Abstract: Volcanic eruptions are important components of natural disturbances that provide a model to explore the effects of volcanic eruption disturbances on soil microorganisms. Despite widespread research, to the best of our knowledge, no studies of volcanic eruption disturbances have investigated the effects on soil microbial communities in the montane meadow steppe. To address this gap, we meticulously investigated the characteristics of the soil microbial communities from the volcano and steppe sites using Illumina MiSeq high-throughput sequencing. Hierarchical clustering analysis and principal coordinate analysis (PCoA) showed that the soil microbial communities from the volcano and steppe sites differed. The diversity and richness of the soil microbial communities from the steppe sites were significantly higher than at the volcano sites ( P < 0.05), and the soil microbial communities in the steppe sites had higher stability. The effects of volcanic eruption disturbances on the bacterial community development are greater than its effects on the fungal communities. The environmental filtering of volcanic eruptions selectively retained some special microorganisms (i.e., Conexibacter, Agaricales, and Gaiellales) with strong adaptability to the environmental disturbances, enhanced metabolic activity for sodium and calcium reabsorption, and increased relative abundances of the lichenized saprotrophs. The soil microbial communities from the volcano and steppe sites cooperate to form complex networks of species interactions, which are strongly influenced by the interaction of the soil and vegetation factors. Our findings provide new information on the effects of volcanic eruption disturbances on the soil microbial communities in the montane meadow steppe. Graphical abstract: Image 1 Highlights: Volcano sites have lower microbial diversity, richness, and stability than steppe sites. The fungal community was more stable after volcanic disturbances than the bacterial community. Volcanic eruptions selectively retained some of the microorganisms with special functions. Microbial networks were mediated by the interaction of the soil and vegetation factors.